2012
DOI: 10.1158/1535-7163.mct-11-0997
|View full text |Cite
|
Sign up to set email alerts
|

Phase I Study of Pazopanib in Combination with Paclitaxel and Carboplatin Given Every 21 Days in Patients with Advanced Solid Tumors

Abstract: Several phase III trials have shown that the addition of an antiangiogenic agent to conventional chemotherapy can improve clinical benefit in patients with advanced solid tumors. This study examined the feasibility of combining pazopanib (Votrient), an oral antiangiogenic agent, with paclitaxel and carboplatin. This 3 þ 3 dose-escalation phase I study evaluated the maximum-tolerated regimen (MTR) of daily pazopanib in combination with paclitaxel 175 mg/m 2 and carboplatin [dosed at area under the curve (AUC) 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
2

Year Published

2013
2013
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 25 publications
0
19
2
Order By: Relevance
“…Previous studies of the combination of pazopanib with weekly paclitaxel have also reported high incidences of fatigue and nausea (25,32); therefore, it is possible that these events could represent potential synergistic toxicities for the combination of pazopanib and paclitaxel. Of note, hematologic toxicity was not dose limiting in this study; this contrasts with the experience with the combination of pazopanib with paclitaxel 175 mg/m 2 and carboplatin AUC 5, in which myelosuppression was the DLT for the combination (23,24). DLTs reported in this study included rash and hepatotoxicity.…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…Previous studies of the combination of pazopanib with weekly paclitaxel have also reported high incidences of fatigue and nausea (25,32); therefore, it is possible that these events could represent potential synergistic toxicities for the combination of pazopanib and paclitaxel. Of note, hematologic toxicity was not dose limiting in this study; this contrasts with the experience with the combination of pazopanib with paclitaxel 175 mg/m 2 and carboplatin AUC 5, in which myelosuppression was the DLT for the combination (23,24). DLTs reported in this study included rash and hepatotoxicity.…”
Section: Discussioncontrasting
confidence: 63%
“…In addition, preclinical evidence suggested the possibility of synergy from the combination of antiangiogenic agents with taxanes (21), and recent data suggested synergism between paclitaxel and pazopanib via inhibition of aurora A in anaplastic thyroid cancer (22). Previous studies demonstrated that pazopanib could not be readily combined with paclitaxel 175 mg/m 2 and carboplatin area under the plasma drug concentration curve (AUC) 5 administered every 3 weeks at doses higher than pazopanib 200 mg (23,24). However, it was feasible to administer pazopanib 800 mg with a weekly regimen of paclitaxel 80 mg/m 2 , which resulted in a 26% higher geometric mean paclitaxel AUC that was similar to the systemic exposure of a paclitaxel dose of 100 mg/m 2 (25).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, one important concern of combining topotecan and pazopanib is the tolerability and toxicity of both drugs, especially the combination, in the clinic (13,14,37). In contrast, current clinical data suggest that CRLX101 is tolerable in combination with standard doses of bevacizumab in patients (38,39).…”
Section: Discussionmentioning
confidence: 99%
“…In the past 30 years, the surgery treatment and radical tumor cells destroy in the early phase ovarian cancer (phase I and II) or advanced cases (phase III and phase IV) using combined chemotherapy based on cisplatin make the patients have better prognosis, but the 5-year survival rate is still around 5-30%. Into the 1990s, as the clinical application of paclitaxel, paclitaxel, cisplatin replace cisplatin, cyclophosphamide combined chemotherapy as the post-surgery first-line treatment of ovarian cancer, prolongs the median survival time in advanced cases, to decrease the poisonousness of the PT scheme, carboplatin was used to replace cisplatin combine paclitaxel therapy, carboplatin is the second generation of platinum antitumor drugs, it's mechanism of action is the same with cisplatin, but the reaction of gastrointestinal tract and renal toxicity is lower than cisplatin (Burris et al, 2012;Kumagai et al, 2011;Mundhenke et al, 2008). Because of the advantages of patient tolerance, do not need to be hydrated, currently accepted by a lot of doctors and patients, at present the paclitaxel combine carboplatin therapy is the postsurgery first-line treatment of ovarian epithelial carcinoma at home and abroad (Harano et al, 2014).…”
Section: Discussionmentioning
confidence: 99%